Tin diselenide-based saturable absorbers for eye-safe pulse lasers. (10th April 2019) - Wang, Mengxia; Wang, Zhengping; Xu, Xinguang; Duan, Sihou; Du, Chenlin
Abstract: Eye-safe pulse lasers have attracted increasing attention due to their potential wide application in many fields. However, optical modulators with excellent nonlinear optical absorption properties in the range of 1.4–2.1 μ m are still very scarce. In this study, tin diselenide (SnSe2 ), a newly-developed 2D layered semiconductor material with facile processability and low cost, was investigated. The nonlinear optical response of SnSe2 was investigated using the open aperture Z-scan method at 1500 and 1800 nm. Using SnSe2 as the saturable absorber, a passive Q-switched solid-state laser was realized at 1.3 and 1.9 μ m for the first time. This study proved SnSe2 to be an effective optical modulating material for the eye-safe waveband.